2006
DOI: 10.1021/jp057275r
|View full text |Cite
|
Sign up to set email alerts
|

Adenine Tautomers:  Relative Stabilities, Ionization Energies, and Mismatch with Cytosine

Abstract: In this study, we have investigated 12 tautomers of the DNA base adenine at the BP86/TZ2P and BP86/QZ4P levels of density functional theory. The vertical and adiabatic ionization energies of all tautomers were determined as the difference in energy between the radical cation and the corresponding neutral system. Furthermore, an evaluation is made for the eigenvalue spectra calculated with the SAOP functional, which is shown to lead to substantial improvements for orbital energies compared to BP86. We have also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(54 citation statements)
references
References 64 publications
4
50
0
Order By: Relevance
“…The intramolecular proton transfer schemes for isolated DNA bases are displayed in Figure 2. The MP2/6-311++G(2df,pd)//B3LYP/6-311++G(d,p) reaction barriers for the forward tautomerisation are 45.58 (Ade), 39.09 (Thy), 38.47 (Cyt) and 32.17 kcal/mol (Gua) and these values tightly correlate with the literature data (Basu et al, 2005;Brovarets' & Hovorun, 2010aDanilov et al, 2005;Fan et al, 2010;Fogarasi & Szalay, 2002;Fogarasi, 2008;Fonseca Guerra et al, 2006;Gorb & Leszczynski, 1998a, 1998bGorb et al, 2001;Gu & Leszczynski, 1999;Hanus et al, 2003Hanus et al, , 2004Kosenkov et al, 2009;Mejía-Mazariegos & Hernández-Trujillo, 2009;Saha et al, 2006). Very large kinetic barriers for intramolecular tautomerisation of all isolated DNA bases (above 32 kcal/mol) indicate that such tautomerisation will be very slow and this process may not occur readily in the isolated molecule.…”
Section: Intramolecular Tautomerisation Of the Dna Basessupporting
confidence: 85%
See 3 more Smart Citations
“…The intramolecular proton transfer schemes for isolated DNA bases are displayed in Figure 2. The MP2/6-311++G(2df,pd)//B3LYP/6-311++G(d,p) reaction barriers for the forward tautomerisation are 45.58 (Ade), 39.09 (Thy), 38.47 (Cyt) and 32.17 kcal/mol (Gua) and these values tightly correlate with the literature data (Basu et al, 2005;Brovarets' & Hovorun, 2010aDanilov et al, 2005;Fan et al, 2010;Fogarasi & Szalay, 2002;Fogarasi, 2008;Fonseca Guerra et al, 2006;Gorb & Leszczynski, 1998a, 1998bGorb et al, 2001;Gu & Leszczynski, 1999;Hanus et al, 2003Hanus et al, , 2004Kosenkov et al, 2009;Mejía-Mazariegos & Hernández-Trujillo, 2009;Saha et al, 2006). Very large kinetic barriers for intramolecular tautomerisation of all isolated DNA bases (above 32 kcal/mol) indicate that such tautomerisation will be very slow and this process may not occur readily in the isolated molecule.…”
Section: Intramolecular Tautomerisation Of the Dna Basessupporting
confidence: 85%
“…In all of these studies, it was suggested that the 9H amino tautomer of Ade is the dominant contributor to the spectra. The experimental results agree closely with calculations at different levels of theory and consistently show the 9H amino tautomer to be the most stable one (Brovarets' & Hovorun, 2011b;Hanus et al, 2004;Fonseca Guerra et al, 2006;Kwiatkowski & Leszczynski, 1992;Norinder, 1987;Nowak et al, 1989bNowak et al, , 1991Nowak et al, , 1994aNowak et al, , 1994bNowak et al, , 1996Sabio et al, 1990;Saha et al, 2006;Sygula & Buda, 1983;Wiorkiewicz-Kuczera & Karplus, 1990).…”
Section: Mutagenic Tautomers Of Dna Basessupporting
confidence: 82%
See 2 more Smart Citations
“…Furthermore, adenine can exist in different tautomeric forms with the most stable one being the 9H-amino tautomer ( Figure 1). [13][14][15] Protonation of the 9H-tautomer usually takes place at the N1 nitrogen. 11,[16][17][18][19][20] By contrast, while N 6 -benzyladenine 21 and kinetin 22 crystallize in the expected 9H-tautomeric form, the N3-protonated 7H-tautomer ( Figure 1) was observed in the crystal structures of their bromide, chloride and dihydrogenphosphate salts.…”
Section: Introductionmentioning
confidence: 99%